Long-Term Supplementation of Ozonated Sunflower Oil Improves Dyslipidemia and Hepatic Inflammation in Hyperlipidemic Zebrafish: Suppression of Oxidative Stress and Inflammation against Carboxymethyllysine Toxicity - Kyung-Hyun Cho; Ji-Eun Kim; Ashutosh Bahuguna; Dae-Jin Kang (MDPI AG, 2023)
Ozonated sunflower oil (OSO) is a well-known functional oil with antioxidant, antimicrobial, anti-allergic, and skin-moisturizing properties. However, studies on the effects of OSO on high-cholesterol diet (HCD)-induced metabolic disorders have been scarce. In the current study, we aimed to determine the anti-inflammatory effects of OSO on lipid metabolism in adult hypercholesterolemic zebrafish and its embryos. Microinjection of OSO (final 2%, 10 nL) into zebrafish embryos under the presence of carboxymethyllysine (CML, 500 ng) protected acute embryo death up to 61% survival, while sunflower oil (final 2%) showed much less protection at around 42% survival. The microinjection of OSO was more effective than SO to inhibit reactive oxygen species (ROS) production and apoptosis in the CML induced embryo toxicity. Intraperitoneal injection of OSO under the presence of CML protected acute death from CML-induced neurotoxicity with improved hepatic inflammation, less detection of ROS and interleukin (IL)-6, and lowering blood total cholesterol (TC) and triglyceride (TG), while the SO-injected group did not protect the CML-toxicity. Long-term supplementation of OSO (final 20%, wt/wt) with HCD for 6 months resulted in higher survivability than the HCD alone group or HCD + SO group (final 20%, wt/wt) with significant lowering of plasma TC and TG levels. The HCD + OSO group showed the least hepatic inflammation, fatty liver change, ROS, and IL-6 production. In conclusion, short-term treatment of OSO by injection exhibited potent anti-inflammatory activity against acute neurotoxicity of CML in zebrafish and their embryo. Long-term supplementation of OSO in the diet also revealed the highest survivability and blood lipid-lowering effect through potent antioxidant and anti-inflammatory activity.